The Generic Science Skill Profile of Fourth Grade Students on Acid And Base Topic in Guided Inquiry Learning Model - Yohana, Ismi; Sudarmin, Sudarmin; Wardani, Sri; Mohyaddin, Siti Norasikin Binti (International Journal of Active Learning, 2018)
This research aims to find and identify the 4th level students science generic skill using guided inquiry learning in SMK Raja Permaisuri Bainun. This research method is descriptive qualitative method that explains the generic science skills indicators that have been studied through the Data taken from the research then Analyzed and summarized as research results. Profile of generic science skills valuation indicates that the indicator of student observation on acid and base material is high with the average of 81. Science Generic skills of symbolic language are classified with average of 73, while logical consistency and inference indicator are classified as high with average of 67 and 85 respectively. Overall, 4th Generic science skills of SMK Raja Permaisuri Bainin on acid and base material in guided inquiry learning is high enough with the average of 76.5. The analysis of students' cognitive learning outcomes guided inquiry learning was obtained in average of 73 and it indicated a high level of achievement. Furthermore, this result also indicated resources in the student's response to the guided inquiry learning that positively influences the students science generic skills.